2005
DOI: 10.1111/j.1365-2036.2005.02408.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term follow‐up of Helicobacter pylori eradication therapy in Vietnam: reinfection and clinical outcome

Abstract: SUMMARYAim: To assess the long-term Helicobacter pylori reinfection rates, as well as the clinical outcome in peptic ulcer disease patients in Vietnam. Method: At a 1-year evaluation of H. pylori eradication treatment in 226 peptic ulcer patients, long-term H. pylori status was assessed with serology and/or culture, peptic ulcer status by gastroscopy, and DNAfingerprinting performed with random amplified polymorphic DNA and restriction fragment polymorphism. Result: Follow-up was performed a mean 11 months aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 32 publications
1
23
1
1
Order By: Relevance
“…Low recurrence rate have been reported from South-east Asia (0%), China (1.1%) and Chile (4.2%) [9, 19, 20], but studies in some other countries have found much higher recurrence rates. In Vietnam, a mean follow-up of 11 months revealed a recurrence rate of 23.5% [21] and in Brazil the re-infection rate one year after eradication was 7.6% [22]. Recurrence rates in these reports are much higher than those reported from developed countries.…”
Section: Discussioncontrasting
confidence: 47%
“…Low recurrence rate have been reported from South-east Asia (0%), China (1.1%) and Chile (4.2%) [9, 19, 20], but studies in some other countries have found much higher recurrence rates. In Vietnam, a mean follow-up of 11 months revealed a recurrence rate of 23.5% [21] and in Brazil the re-infection rate one year after eradication was 7.6% [22]. Recurrence rates in these reports are much higher than those reported from developed countries.…”
Section: Discussioncontrasting
confidence: 47%
“…The well-documented incidence of recurrent infection after antibiotic eradication in adults and children suggests that even adults continue to be exposed to H. pylori, at least in regions where the levels of infection are high (26,47,56). One patient in our study exhibited heterogeneity with all three tests for macrodiversity.…”
Section: Discussionmentioning
confidence: 74%
“…Spouse-spouse transmission would appear to be an obvious source of infection in adulthood [16,29] . In areas where the risk of contamination is high, reinfection can be prevented by eradication programs [30,31] . Lifestyle changes are recommended, but they are unlikely to occur in the short term.…”
Section: Discussionmentioning
confidence: 99%